Understanding Privacy Paradox in Social Media among Adolescents from Religious Perspectives - Zainab Ibrahim, Siti; Masrom , Maslin; Radin Salim, Kamilah (International Journal of Psychosocial Rehabilitation, 2020)
Social norms and individual characters of Malaysians are mainly shaped by religious elements. Depending on how religion is being perceived by an individual, it shapes one’s attitudes toward social media and hence affects how one discloses personal information on social media. Using a moderated mediation approach, this study examines the roles of perceived benefits and privacy risks in using social media as predictors of the information disclosure behaviors mediated by religious orientations and ethnicity as a moderator that influences the strength of the implied indirect effect. A survey study was conducted involving 471 students from nine secondary schools in the southern region of Malaysia. The result shows that certain types of information disclosure behaviors in social media that were significantly mediated by religious orientations could be predicted by the proposed benefits and privacy risks perceived from using the media, such that the predictions varied across ethnic groups. The implications of religion and ethnicity on users’ attitudes and behaviors in social media are discussed.